The Relationship Between Nurses' Knowledge And Motivation With The Implementation Of Patient Safety - Risa Dhea Puspita; Etlidawati Etlidawati; Deisy Sri Hardini; Wahyu Riyaningrum (Jurnal Keperawatan Profesional, 2026)
Patient safety serves as a principal benchmark for appraising the caliber of hospital care. Nurses' knowledge and motivation function as pivotal determinants that bolster the enactment of patient safety. Data from the Dr. R. Goeteng Taroenadibrata Purbalingga Regional General Hospital (RSUD) in 2024 recorded 27 patient safety incidents out of a total of 16,896 inpatients (0.16%). This study aims to identify the relationship between nurses' knowledge and motivation with the implementation of patient safety in the inpatient ward of Dr. R. Goeteng Taroenadibrata Purbalingga Regional General Hospital. The investigation employed a numerical methodology coupled with a descriptive-correlational framework and a cross-sectional orientation. The cohort of the inquiry bercomprised 38 nursing personnel recruited via a total-enumeration procedure. The measurement tool included a questionnaire on nurses' knowledge, motivation, and implementation of patient safety. Data analysis was examined through a Chi-Square procedure yielding a p-value <0.05. The findings revealed that the greater proportion of participants possessed good knowledge (81.6%), high motivation (65.8%), and good implementation of patient safety (65.8%). The Chi-Square test showed a significant relationship between knowledge and implementation of patient safety with a p value of 0.004 (p < 0.05) and a relationship between nurse motivation and implementation of patient safety with a p value of 0.003 (p < 0.05). Thus, an association exists between nurse knowledge and motivation with the implementation of patient safety in the inpatient ward of Dr. R. Goeteng Taroenadibrata Purbalingga Regional General Hospital.